Emergence of a distinct HIV‐specific IL‐10‐producing CD8+ T‐cell subset with immunomodulatory functions during chronic HIV‐1 infection. Issue 11 (29th August 2013) - Clutton, Genevieve; Yang, Hongbing; Hancock, Gemma; Sande, Nellia; Holloway, Cameron; Angus, Brian; von Delft, Annette; Barnes, Eleanor; Borrow, Persephone; Pellegrino, Pierre; Williams, Ian; McMichael, Andrew; et al.
<x xml:space="preserve">Abstract</x> Interleukin‐10 (IL‐10) plays a key role in regulating proinflammatory immune responses to infection but can interfere with pathogen clearance. Although IL‐10 is upregulated throughout HIV‐1 infection in multiple cell subsets, whether this is a viral immune evasion strategy or an appropriate response to immune activation is unresolved. Analysis of IL‐10 production at the single cell level in 51 chronically infected subjects (31 antiretroviral (ART) naïve and 20 ART treated) showed that a subset of CD8+ T cells with a CD25neg FoxP3neg phenotype contributes substantially to IL‐10 production in response to HIV‐1 gag stimulation. The frequencies of gag‐specific IL‐10‐ and IFN‐γ‐producing T cells in ART‐naïve subjects were strongly correlated and the majority of these IL‐10+ CD8+ T cells co‐produced IFN‐γ; however, patients with a predominant IL‐10+/IFN‐γneg profile showed better control of viraemia. Depletion of HIV‐specific CD8+ IL‐10+ cells from PBMCs led to upregulation of CD38 on CD14+ monocytes together with increased IL‐6 production, in response to gag stimulation. Increased CD38 expression was positively correlated with the frequency of the IL‐10+ population and was also induced by exposure of monocytes to HIV‐1 in vitro. Production of IL‐10 by HIV‐specific CD8+ T cells may represent an adaptive regulatory response to monocyte activation during chronic infection.